2022
DOI: 10.1039/d2cp02601e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the mitigation of Aβ aggregation and protofibril destabilization by ad-enantiomeric decapeptide rk10

Abstract: According to clinical studies, the development of Alzheimer’s disease (AD) is linked to the abnormal aggregation of amyloid-β (Aβ) peptides into toxic soluble oligomers, protofibrils as well as mature fibrils....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 117 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Altogether, these results reflect that the binding of αBC to the Aβ 42 monomer is mainly driven by polar, hydrophobic, and H-bonding interactions. Apart from αBC, other inhibitors, such as gallic acid and its derivatives and short peptides, have also shown multiple binding modes in binding to the Aβ 42 peptide. …”
Section: Resultsmentioning
confidence: 99%
“…Altogether, these results reflect that the binding of αBC to the Aβ 42 monomer is mainly driven by polar, hydrophobic, and H-bonding interactions. Apart from αBC, other inhibitors, such as gallic acid and its derivatives and short peptides, have also shown multiple binding modes in binding to the Aβ 42 peptide. …”
Section: Resultsmentioning
confidence: 99%
“…The amino acid sequence of the Aβ42 monomer, Aβ42 dimer, and Aβ42 tetramer is DAEFRHDSGY 10 EVHHQKLVFF 20 AEDVGSNKGA 30 IIGLMVGGVV 40 IA. 26 In this study, the initial Aβ42 monomer structure was taken from the populated cluster from a preceding 3 μs MD simulation of monomeric Aβ42 in solution, which comes from the work by Fatafta et al 31 The initial 3D structure of the Aβ42 tetramer protofibril was obtained from the Protein Data Bank (https://www.rcsb.org/, PDB ID: 5OQV), which was generated by cryo-electron microscopy in combination with solid-state NMR data. 22 Notably, Zhan et al 62 have demonstrated that the tetramer is the smallest stable nucleus of Aβ42 protofibrils.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to available experimental technologies, it is still challenging to systematically visualize the structure and self-assembly process of Aβ42 peptides under various conditions. Molecular simulations, on the contrary, may offer some useful information from the microscopic view, which have been extensively employed in this field. For example, Fatafta et al performed microsecond-scale molecular dynamics (MD) simulations to explore the dynamic behavior of the Aβ42 dimer in different environments and found that the secondary structure of the Aβ42 dimer exhibited a transition from a random coil to a β-sheet in solution, but it was inhibited to some extent in the presence of lipid bilayers. Man et al reported an all-atom MD simulation study on Aβ42 dimers, trimers, and tetramers.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations have been extensively used to gain molecular-level insights into the interactions of NPs with amyloid fibrils involved in NDs. [30][31][32][33][34][35][36][37] In this study, to gain a detailed molecular understanding of oxidized EGCG binding into the hydrophobic remodeling process, we investigated the binding between oxidized EGCG and ThT to the hydrophobic core of a pathogenic a-syn fibril using molecular docking calculations and molecular dynamics (MD) simulation. We included ThT molecules as ligands in our computational approach since ThT competes for the same binding site as that of EGCG in the a-syn fibrils, but their binding does not alter the fibril structure.…”
Section: Introductionmentioning
confidence: 99%